MODEL TINGKAT PRODUKSI EKONOMIS DENGAN PROSES PENGERJAAN ULANG DAN PADA TINGKAT PELAYANAN TERJADI KEKURANGAN PERSEDIAAN - Reza Budiman; Tumpal P. Nababan; Endang Lily (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article studies the economic production quantity (EPQ). During the production process, the failures occur and reworking is conducted to minimize the total production cost. This study is a review of Chiu et. al [Mathematical and Computational Applications, 11(2006): 75-84]. A numerical example is given to explain the problem discussed.